BETWEEN POLICY AND PREFERENCE: THE STRUGGLE OF VERTICAL HOUSING IN BANDUNG - Luqman, Rashif Imaduddin; Abadi, Agustinus Adib; Siregar, Mohammad Jehansyah; Yuwono, Tri; Sekartaji, Dian; Isnandya, Adhitya Rizky; Liandrawani, Novi; Mawarsari, Daffa (International Journal on Livable Space, 2026)
Despite strong policy support, vertical housing in Bandung struggles to gain public acceptance. This reveals a significant gap between policy goals and residents’ experiences, which shape their long-term housing preferences. Aims: The study identifies the key economic, socio-spatial, and institutional factors that predict resident satisfaction and influence the decision to leave vertical housing. Methodology and results: Using a mixed-methods comparative design was used, including a survey of 75 residents. The results show that institutional factors, such as low management satisfaction (mean < 3.1/5) and infrastructure issues, are the primary drivers of dissatisfaction. Commercial residents prioritize transactional attributes, such as location and aesthetics, while rental flat residents apply a communal logic, linking satisfaction to their entire living environment. Conclusion, significance, and impact of the study: The study reveals a striking convergence: the majority of residents in both commercial (72%) and public rental flats (62%) desire to move to landed housing. This indicates a policy Implementation dilemma, where failures in management and maintenance push residents to desire moving back to landed houses, which in turn undermines the policy's goal of curbing urban sprawl.